Bifenilos policlorados (PCBs) em milho e farinha de milho do estado do Rio Grande do Sul - Schwanz, Thiago Guilherme (2011)
The polychlorinated biphenyls (PCBs) production and trading are prohibited in whole world, due its high toxicity. These aromatic compounds were industrially used since the 30 s decade. Significant physics characters, as a high temperature and electric current tolerance, are responsible for the PCBs large employment and worldwide production. Mainly due for the old electric equipments inappropriate discard, a large part of this production came in to the environment, contaminating the soil and water. They are non-biodegradable compounds that becoming accumulated in the environment and in the food chain. They toxic human effects was evidenced from realized studies, and the contaminated food ingestion is the mainly route of exposure to PCBs. The cereals are an essential part of our nutrition, due this human survives historical significance. The corn receives a large notability among the cereals, being the most consumed grain in the world. Due to this, and to the PCBs persistent and malignant effects to human, the objective of this work was to determinate the PCBs levels in corn and cornflour from different regions of Rio Grande do Sul State, collected on 2009 and 2010 years, checking the connect of these levels with the collected region, year of harvest, lipid content and the flour type. The PCBs residues were determinate by gas chromatography coupled with mass spectrometer (GC-MS), using electron impact ionization and a negative chemical ionization, before ultrasonic extraction of the compounds. The mean values detected were 0.01 ng g-1 to the PCB 10, 0.04 ng g-1 to the PCB 28, 0.10 ng g-1 to the PCB 52, 0.14 ng g-1 to the PCB 153, 0,40 ng g-1 to the PCB 138 and 0,38 ng g-1 to the PCB 180. The most frequent was the PCB 138, which was detected in 63,47% of the samples, followed by the PCBs 180 (58.27%), 52 (41.72%), 153 (41.05%), 28 (20.52%) and 10 (7.28%). The samples from the northeast and metropolitan regions showed the higher concentrations. Besides it, there was a decrease in the contamination on the year of 2010 when compared with 2009. Another significant factor was the high contamination detected in the cornflours in relation to the grain, with significantly differences for the PCBs 52, 138, 153 and 180. Concerning about the flour analyses, the fact of the PCBs have a great fat attractive force was confirmed, with all the PCBs congeners showed significant difference in the correlation with their lipid levels.